Intervensi Sosial dalam Manajemen Pendidikan Inklusif Dinas Pendidikan Kebudayaan Kepemudaan dan Olahraga Kabupaten Semarang - Thea Rahmanindita; Titik Djumiarti (Universitas Serang Raya, 2021)
The implementation of inclusive education in Semarang is still experiencing various obstacles. The aim of this research is to analyze the social intervention conducted by the Education Office, Culture, Youth and Sports District of Semarang in the implementation of an inclusive education of elementary school level, by looking at the intervention process carried out and the constraints contained therein. This research uses qualitative methods of descriptive. The results showed that the management of inclusive education in Semarang Regency isn’t optimal, because there is still an intervention process that is not seen in the implementation of inclusive education by the Semarang District Education Office. The advice that researchers can provide is the addition of quotas for the ABK to school and the addition of budgets intended for the recruitment process of special escort teachers, special escort teachers ' benefit, procurement of infrastructure and maintenance. Keywords: Social intervention, management, inclusive education